Leishmania kinetoplast DNA contributes to parasite burden in infected macrophages: Critical role of the cGAS-STING-TBK1 signaling pathway in macrophage parasitemia - Yilmaz, Ismail Cem; Dunuroglu, Emre; Ayanoglu, Ihsan Cihan; Ipekoglu, Emre Mert; Yildirim, Muzaffer; Girginkardesler, Nogay; Ozbel, Yusuf; Toz, Seray; Ozbilgin, Ahmet; Aykut, Gamze; Gursel, Ihsan; Gursel, Mayda (Frontiers in Immunology, 2022)
Leishmania parasites harbor a unique network of circular DNA known as kinetoplast DNA (kDNA). The role of kDNA in leishmania infections is poorly understood. Herein, we show that kDNA delivery to the cytosol of Leishmania major infected THP-1 macrophages provoked increased parasite loads when compared to untreated cells, hinting at the involvement of cytosolic DNA sensors in facilitating parasite evasion from the immune system. Parasite proliferation was significantly hindered in cGAS- STING- and TBK-1 knockout THP-1 macrophages when compared to wild type cells. Nanostring nCounter gene expression analysis on L. major infected wild type versus knockout cells revealed that some of the most upregulated genes including, Granulysin (GNLY), Chitotriosidase-1 (CHIT1), Sialomucin core protein 24 (CD164), SLAM Family Member 7 (SLAMF7), insulin-like growth factor receptor 2 (IGF2R) and apolipoprotein E (APOE) were identical in infected cGAS and TBK1 knockout cells, implying their involvement in parasite control. Amlexanox treatment (a TBK1 inhibitor) of L. major infected wild type cells inhibited both the percentage and the parasite load of infected THP-1 cells and delayed footpad swelling in parasite infected mice. Collectively, these results suggest that leishmania parasites might hijack the cGAS-STING-TBK1 signaling pathway to their own advantage and the TBK1 inhibitor amlexanox could be of interest as a candidate drug in treatment of cutaneous leishmaniasis.